The Ecological Status of European Rivers: Evaluation and Intercalibration of Assessment Methods 2006
DOI: 10.1007/978-1-4020-5493-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Macrophyte communities of European streams with altered physical habitat

Abstract: The impact of altering hydro-morphology on three macrophyte community types was investigated at 107 European stream sites. Sites were surveyed using standard macrophyte and habitat survey techniques (Mean Trophic Rank Methodology and River Habitat Survey respectively). Principal Components Analysis shows the macrophyte community of upland streams live in a more structurally diverse physical habitat than lowland communities. Variables representing the homogeneity and diversity of the physical environment were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Nevertheless, macrophytes were introduced into freshwater monitoring as indicators of river degradation, especially of more persistent and constant habitat changes, which can integrate the long-term effects of disturbances (Westlake, 1975;Smolders et al, 2001;Ceschin et al, 2010). Macrophyte-based methods focus mainly on the determination of eutrophication (e.g., Holmes et al, 1999;Meilinger et al, 2005;Haury et al, 2006;Szoszkiewicz et al, 2006Szoszkiewicz et al, , 2010bSchneider, 2007;Willby et al, 2009;Gebler et al, 2014) or acidification (Tremp & Kohler, 1995;O'Hare et al, 2006). However, macrophyte methods are also used to assess river degradation in a more holistic or integrative way (Passauer et al, 2002;Schaumburg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, macrophytes were introduced into freshwater monitoring as indicators of river degradation, especially of more persistent and constant habitat changes, which can integrate the long-term effects of disturbances (Westlake, 1975;Smolders et al, 2001;Ceschin et al, 2010). Macrophyte-based methods focus mainly on the determination of eutrophication (e.g., Holmes et al, 1999;Meilinger et al, 2005;Haury et al, 2006;Szoszkiewicz et al, 2006Szoszkiewicz et al, , 2010bSchneider, 2007;Willby et al, 2009;Gebler et al, 2014) or acidification (Tremp & Kohler, 1995;O'Hare et al, 2006). However, macrophyte methods are also used to assess river degradation in a more holistic or integrative way (Passauer et al, 2002;Schaumburg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophytes can have dramatic effects on the physical structure of aquatic habitats (O'Hare et al, 2006;Smokorowski and Pratt, 2007) and create a heterogeneous mosaic at different scales. Some studies have suggested that structural heterogeneity of macrophytes mediates trophic interactions among various biota (Jeppesen et al, 1997;Pelicice and Agostinho, 2006) and significantly influences the biodiversity of the zooplankton community (Tolonen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In empirical studies, macrophytes can have dramatic effects on freshwater habitat structures (O'Hare et al, 2006;Smokorowski and Pratt, 2007), and provide a heterogeneous mosaic at different scales. Therefore, macrophytes are capable of providing habitat suitable for colonization by zooplankton, including D. brachyurum.…”
Section: Discussionmentioning
confidence: 99%